ESTUDO DA SUBSTITUIÇÃO DE Nb2O5 POR Sb2O3 E EFEITO DA CALCINAÇÃO SOBRE A MICROESTRUTURA E PROPRIEDADES ELÉTRICAS DE VARISTORES DE SnO2 - Ciórcero, Juliane Rutckeviski (2011)
This work studied systematically the substitution of Nb2O5 by Sb2O3 in composition of a ternary varistor system and study of calcination of binary and multi-component systems and their relationship microstructure-electric property. In part I of the work, study of substitution of Nb2O5 by Sb2O3, the compositions were prepared by conventional ceramic processing and dried by "spray-dryer" Pellets were produced at 25 MPa and sintering was produced at 1350ºC/ 2h.Increasing the concentration of Sb2O3, the nonlinear behavior of ceramics was reduced, accompanied by the reduction of the breakdown electric field and increased leakage current. With increasing concentration of 0.05% Sb2O3 to 0.5% (mol%), the samples were more porous, suggesting that higher concentrations of Sb2O3 decreases the rate of sintering. This decrease was linked to the increased concentration of tin vacancies that leads to nondensifying processes. In part II, was studied the influence of calcination (700oC, 1000oC and 1200oC) of binary and multi-component systems. The compositions were prepared by the conventional method, with the addition of the calcination process. The samples were comformed at 75 MPa and sintered at 1300oC for systems calcined at 1200oC and 1300oC, and at 1350oC for systems calcined at 700oC and 1000oC. Some studied systems have showed cassiterite phase associated to the SnO phase. With the addition of dopants, there was an increase in density of the systems, and the increase in temperature of sintering also led to a slight increase in density. The addition of chromium to systems calcined at 700oC and 1000oC led to a decrease in the breakdown electric field, with the exception of the systems 99.5% +0.5% Sb2O3 + 0.5% Co3O4 e 99.5% +0.5% Sb2O3 + 0.5% Co3O4 (excess) + 0.05% Cr2O3 (excess), where there was a decrease of breakdown electric field with the addition of chromium, and this can be explained because of their densities. All samples calcined at 1200oC regardless of the composition, showed very similar microstructure, high porosity and small grain size. The sample that presented the best varistor behavior with the lower leakage current was the FCC25% (75% of varistor formulation, 99,4%SnO2. 0,5%Co3O4. 0,05%Nb2O5. 0,05%Cr2O3 and 25% of conductive formulation, 99,0%SnO2. 0,5%Co3O4. 0,5%Sb2O3).